AN ANALYSIS OF SCHOOL PRINCIPALS' PERCEPTIONS OF TEACHER COMPETENCE AND THE ATTRIBUTION OF LOW LEARNING QUALITY - Winda Nopriani; Abdullah Idi; Tutut Handayani; Afriantoni Afriantoni (Jurnal Konseling Pendidikan Islam, 2026)
This study aimed to analyze the principal’s perceptions of teacher competence and the principal’s attribution of the low quality of learning at SMA Negeri 1 Talang Ubi, Penukal Abab Lematang Ilir Regency. The study focused on the principal’s perceptions of four teacher competencies, namely pedagogical, professional, personal, and social competencies, as well as how the principal attributed the factors causing the low quality of learning originating from both internal and external school factors. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with the principal as the main informant, classroom observations, and documentation studies of learning devices and relevant school documents. Data analysis was conducted using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification. Data trustworthiness was ensured through credibility, transferability, dependability, and confirmability tests by applying triangulation and member checking. The results showed that the principal generally had a positive perception of teacher competence in pedagogical, professional, personal, and social aspects. However, improvements were still required in terms of learning innovation and adaptation to evolving educational policies. The principal also attributed the low quality of learning relatively evenly to internal and external factors. Internal factors were related to teachers’ readiness and adaptability in implementing learning processes, while external factors included student characteristics, parental involvement, and limitations in school facilities and educational regulations. These findings indicate that the principal has an objective and constructive perspective in addressing issues related to learning quality and in formulating improvement efforts.